STRATEGI PENJUALAN KOPI KOPITALISME DI MASA PANDEMI - Rena Angga Saputra; Mohamad Farchan Albariqi (LPPM Universitas Bina Bangsa, 2022)
There is a new trend in lifestyle, where when a certain person or group discusses something, they tend to prefer to discuss it in a comfortable and relaxed place. One of them is a coffee shop. The purpose of this study was to examine the strategy of selling coffee for coffee during the pandemic. This type of research is a qualitative research. Time and Location. This research was conducted in the city of Surabaya, which is in the province of East Java. The research started in August to December 2021. The results showed There are many advantages of capitalism compared to others which can then be used as opportunities. Based on the SWOT analysis, there are several suggestions of strategies suggested by researchers so that capitalism can increase its profits and be able to survive in a market with intense competition